Delaying meiotic resumption during transportation of bovine cumulus-oocyte complexes: Effects on development, apoptosis and caspases activity of in vitro-produced embryos - Dall'Acqua, Priscila Chediek [UNESP]; Leão, Beatriz Caetano Da Silva [UNESP]; Rocha-Frigoni, Nathália Alves De Souza [UNESP]; Gottardi, Fernanda Patrícia; Mingoti, Gisele Zoccal [UNESP] (Cambridge University Press (CUP), 2017)
This study examined the effects of meiosis inhibition during bovine oocyte transportation on developmental competence and quality of produced embryos. The transportation medium was supplemented with: 100 μM butyrolactone I (BL), 500 μM IBMX + 100 μM forskolin (mSPOM), 100 μM milrinone (MR) or follicular fluid (bFF), and was carried out in a portable incubator for 6 h. Next, oocytes were in vitro matured (IVM) for 18 h, without the meiotic inhibitors, with the exception of mSPOM group, in which was added 20 μM cilostamide. The three control groups were IVM with 10% fetal calf serum (FCS) (Control Lab FCS) or 0.6% bovine serum albumin (BSA) (Control Lab BSA) in a CO2 in air incubator or in the portable incubator with 0.6% BSA (Control Transp BSA). Higher cleavage rates (P < 0.05) were obtained in the Control Lab FCS group (84.5 ± 5.3%) compared with the other groups (59.6 ± 3.4% to 70.9 ± 2.3%). Embryonic development was higher (P < 0.05) in the Control Lab FCS group (39.8 ± 4.7%) than in the Control Transp BSA (22.7 ± 3.4%) and MR (21.6 ± 2.3%) groups. However, they were similar (P > 0.05) to the other groups (23.6 ± 3.3% to 28.8 ± 2.7%). The total number of blastomeres was higher (P < 0.05) in the Control Lab FCS group (85.2 ± 5.6) than in Control Lab BSA (53.6 ± 2.9), Control Transp BSA (55.5 ± 4.4), BL (58.2 ± 3.0), mSPOM (57.9 ± 4.9) and MR (59.2 ± 3.9), but all these treatments did not differ (P > 0.05) from bFF (67.7 ± 4.2). No differences (P > 0.05) were found in apoptosis by the activity of caspases (139.0 ± 3.2 to 152.4 ± 6.5, expressed in fluorescence intensity) as well as the percentage of TUNEL-positive cells (12.3 ± 2.0% to 15.7 ± 1.7%). In conclusion, the transportation of oocytes over 6 h with BL, mSPOM or bFF enabled the acquisition of developmental competence at similar rates to the Control Lab FCS group.
Keywords: Developmental competence; In vitro maturation; Meiotic block; Oocyte; Transport